Towards a Practice of Respecting the In-between: Condition Sine Qua Non of Living Together Peacefully - Mulder, Anne-Claire (Feminist theology, 2009)
Living together peacefully in a world of differences asks for a practice of respecting the irreducible difference of the other. Acknowledging this `not-me' of the other subject generates an in-between: a space/time between subjects that cannot be transgressed other than by violence. Following Irigaray, I argue that this `in-between' comes about through the passion of wonder, a being touched in the flesh in the encounter with the other, which opens the subject to him/herself and to the other. To perceive this touch asks for a life-style directed at keeping open and sensitizing the sensibilities of the senses, so that the subject's aesthesis or awareness for the perceptions of the sensible flesh and of its reactions to the other is heightened. Key-element in this aesthetics is the practice of breathing. It enables the subject to remain rooted in him/or herself and open to the other: generating and respecting the in-between between them.